2018
DOI: 10.1039/c8ob01758a
|View full text |Cite
|
Sign up to set email alerts
|

Cesium carbonate-promoted synthesis of aryl methyl sulfides using S-methylisothiourea sulfate under transition-metal-free conditions

Abstract: In the presence of cesium carbonate, an efficient synthesis of aryl methyl sulfides by the reactions of aryl halides with commercially available S-methylisothiourea sulfate is developed. This odourless and highly crystalline solid can be used as the substitute for malodorous methanethiol. The gram-scale reaction also proceeds smoothly without the use of column chromatography separation. Similarly, 2-(dimethylamino)ethylthio and cyclopropylmethylthio groups can be easily introduced into the aromatic rings from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…After removal of the solvent under reduced pressure, the residue was purified by flash column chromatography on silica gel using the mixture of petroleum ether and ethyl acetate (v/v, 30:1 to 10:1) as the eluent to afford the target products 10 . The characterization data for 10c and 10l were agree with our recent published paper …”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…After removal of the solvent under reduced pressure, the residue was purified by flash column chromatography on silica gel using the mixture of petroleum ether and ethyl acetate (v/v, 30:1 to 10:1) as the eluent to afford the target products 10 . The characterization data for 10c and 10l were agree with our recent published paper …”
Section: Methodssupporting
confidence: 91%
“…It was found that the reactions of 1a with phenylmethanethiol ( 8a ) and dodecane‐1‐thiol ( 8b ) afforded the expected products 10a and 10b in 92 % and 93 % yields, respectively. Recently, we have developed an efficient synthesis of aryl alkyl sulfides by the reactions of aryl halides with S ‐alkylisothiourea salts These odorless solids can be simply prepared from alkyl halides and thiourea and can be used as substitutes for malodorous thiols. In the present study, products 10a – 10l were also obtained in excellent yields from 1a and their corresponding S ‐alkylisothiourea salts.…”
Section: Resultsmentioning
confidence: 99%
“…In response to these limitations, the transition metal‐free thiomethylation of aryl halides using DMSO or S‐methylisothiourea (Scheme d) has been described. In these reactions, base‐mediated formation of dimethyl sulfide or methyl sulfide in situ followed by an S N Ar on the halide substrates led to the thiomethyl ether products.…”
Section: Introductionmentioning
confidence: 99%
“…The latter was identified by comparing 1 H-NMR and EI-MS data with the literature. [38,39] It seems that 1a is formed after deprotonation of the coordinated propyne in 5a and subsequent reaction with residual MeI. In the case of the Mo variant, the 1 Table 1.…”
Section: Synthesis Of Carbonyl Complexesmentioning
confidence: 99%